INDONESIAN DECENTRALIZATION IN THE COVID-19 PANDEMIC: ON THE RIGHT TRACK OR NOT? - IRFAN RIDWAN MAKSUM (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2020)
This article aims to ascertain whether decentralization practices in Indonesia are on the right track or not in handling the Covid-19 Pandemic, which demands the presence of roles from both the Central and Local Governments. The background is the tendency of decentralization practices in general in Indonesia, which seems chaotic based on the analysis of the relationship between the Central and Local Governments in handling Covid-19. This writing uses a descriptive qualitative approach with explanations that refer to the theory of decentralization and local autonomy. The data used here are secondary data based on the study of literature derived from electronic publications, documents, or books that are relevant and actual due to the practice of Decentralization in Indonesia. The results of this paper conclude that the practice of decentralization in Indonesia in dealing with the Covid-19 Pandemic is still experiencing a need for certainty in the right direction, specifically related to the effectiveness of handling the Covid-19 outbreak and in general for central-local governance at various Government affairs. The revision of the Local Government Law is the most decisive suggestion here.